Nekotorye aspekty narusheniya venoznogo krovoobrashcheniya u sportsmenov vo vremya dlitel'nykh aviapereletov i pereezdov - Safonov, L. V. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
After airflights or moving by a bus when duration more than 6-8 h at people of various age and irrespective of flebological anamnesis the cases of a thrombophlebitis of deep veins and pulmonary throbomboemboly were marked. Although the venous stasis of a sportsmen after long moving and flights is observed very frequently, however it is rare diagnosed by doctors of teams. The offered measures of active and passive prophylaxis are very effective and allow keeping complete work capacity of sportsmen after long airflights and movings by a bus.